2016
DOI: 10.1155/2016/5029414
|View full text |Cite
|
Sign up to set email alerts
|

A High-Fat, High-Fructose Diet Induces Antioxidant Imbalance and Increases the Risk and Progression of Nonalcoholic Fatty Liver Disease in Mice

Abstract: Excessive fat liver is an important manifestation of nonalcoholic fatty liver disease (NAFLD), associated with obesity, insulin resistance, and oxidative stress. In the present study, the effects of a high-fat, high-fructose diet (HFFD) on mRNA levels and activities of the antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were determined in mouse livers and brains. The histomorphology of the livers was examined and the state of nonenzymatic reducing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 35 publications
6
43
2
7
Order By: Relevance
“…These results agree with Cavarape et al () who recorded downregulation in hepatic Cat and Sod1 expression in HFD‐fed rats. While disagree with the results of Jarukamjorn, Jearapong, Pimson, and Chatuphonprasert () who reported that the mRNA level and enzymatic activity of SOD, CAT, and GPx were increased in liver of mice fed on a high‐fat, HFD for 2–8 weeks. It was reported that transcription factors are sensitive to the changes in the redox state of the cell, so it may be modulated by fructose‐induced oxidative stress (Allen & Tresini, ).…”
Section: Discussioncontrasting
confidence: 89%
“…These results agree with Cavarape et al () who recorded downregulation in hepatic Cat and Sod1 expression in HFD‐fed rats. While disagree with the results of Jarukamjorn, Jearapong, Pimson, and Chatuphonprasert () who reported that the mRNA level and enzymatic activity of SOD, CAT, and GPx were increased in liver of mice fed on a high‐fat, HFD for 2–8 weeks. It was reported that transcription factors are sensitive to the changes in the redox state of the cell, so it may be modulated by fructose‐induced oxidative stress (Allen & Tresini, ).…”
Section: Discussioncontrasting
confidence: 89%
“…11,12 Of note, on one hand, biomechanical experiments and clinical observations have illustrated that long-term intake of HFD results in lipid accumulation and endotoxemia, which can cause increase in inflammatory cytokines in the serum and organs and inflammationrelated signaling activation, promoting the development of nonalcoholic fatty liver disease (NAFLD) and systemic disorder. 11,[13][14][15] On the other hand, HFD significantly increases the production of reactive oxygen species (ROS), which further release superoxide anion and cause oxidative stress in the kidney by stimulating podocyte injury. [15][16][17] Hence, antioxidant therapy may be involved in the pathological process of kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…11,[13][14][15] On the other hand, HFD significantly increases the production of reactive oxygen species (ROS), which further release superoxide anion and cause oxidative stress in the kidney by stimulating podocyte injury. [15][16][17] Hence, antioxidant therapy may be involved in the pathological process of kidney injury. Previous reports show that TLR4/ NF-kB and mitogen-activated protein kinase (MAPK) pathways are involved in cellular inflammation in response to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that mitochondrial lipid accumulation is counted as a major cause of higher cardiac mitochondrial ROS production in HFD feeding models . A previous study has also demonstrated that HFD caused an imbalance between free radicals and antioxidants, with a subsequent increase in mitochondrial ROS levels. Bax protein expression is recruited to the mitochondrial membrane during mitochondrial stress which could be a cause of mitochondrial membrane depolarization .…”
Section: Discussionmentioning
confidence: 98%